2016
DOI: 10.4018/joeuc.2016070101
|View full text |Cite
|
Sign up to set email alerts
|

How does Social Media Analytics Create Value?

Abstract: The surge of interest in big social data has led to growing demand for social media analytics (SMA). Having robust SMA can help firms create value and achieve competitive advantages. However, most firms do not always know how to embrace big social data to establish a path to value. This study addresses this key question to deepen our understanding of how different types of SMA can be applied to create value. Specifically, the findings show the significant uses of opinion mining or sentiment analysis, topic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Prior research indicates that social media data are used in public relations primarily to guide issues, crisis and customer relationship management and to inform strategic Public relations in the age of data communication planning, messaging and evaluation activities (Akter et al, 2016;Colleoni, 2012;Coursaria and van Osch, 2015;Zerfass and Volk, 2018). For example, Wiesenberg et al's (2017, p. 106) research showed that practitioners involved in big data activities use analytics most often to plan overall strategies andto a lesser degreeto measure results to justify communication activities and inform day-to-day actions.…”
Section: Sma In Public Relationsmentioning
confidence: 99%
“…Prior research indicates that social media data are used in public relations primarily to guide issues, crisis and customer relationship management and to inform strategic Public relations in the age of data communication planning, messaging and evaluation activities (Akter et al, 2016;Colleoni, 2012;Coursaria and van Osch, 2015;Zerfass and Volk, 2018). For example, Wiesenberg et al's (2017, p. 106) research showed that practitioners involved in big data activities use analytics most often to plan overall strategies andto a lesser degreeto measure results to justify communication activities and inform day-to-day actions.…”
Section: Sma In Public Relationsmentioning
confidence: 99%
“…Hossain et al (2020) state that process consistency is related to service design, which refers to the consistency of various customer-facing elements that are relevant and comparable within different channels. Itani et al (2022) point out that the consistency relates to both content and process, and the ultimate goal of brands is to maintain this consistency across various channels (Sousa and Voss, 2006; Akter et al , 2016). In Figure 1, consistency is added to highlight that brands need to provide in omni-channel marketing to deliver seamless experience.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inter-disciplinary orientation of SMA, it has been argued to "provide other disciplines -including IS -with methodological foundations for their social media-related research" (Stieglitz et al, 2014: 95). The inter-disciplinary character of SMA has enabled its traction within fields such as IS (Akter et al, 2016;Brant et al, 2017;Chang et al, 2017;Gandomi and Haider, 2015) and innovation management (Laurell & Sandström, 2016Moe and Schweidel, 2017). In addition, it allows scholars from different disciplines to draw from the approach and adapt it to specific purposes in terms of how social media tracking, data preparation and data analysis are designed.…”
Section: Methodsmentioning
confidence: 99%